PANDANGAN FILSAFAT PENDIDIKAN ISLAM DALAM KONSEP PESERTA DIDIK - Tasya Amelia Putri Siregar; Ummi Nadrah Nasution; Salminawati Salminawati (JURNAL TARBIYAH, 2024)
In the essence of human meaning, God created man with a fitrah in his body and spirit. This research advances the philosophical view of the essence of the student's scientific development efforts to realize a perfect human being (Insan Kamil). In his literature, this study uses the concept of library research as a guideline in literary review. Thus, the results of this research relate to the students in the perspective of the philosophy of Islamic education by merging the concept of the essence of man as the actualization of the tasks, responsibilities and characteristics that must be possessed by the students.